(untitled) (Per Musi, 2023)
This work presents an overview of the evolution and the multiplicity of percussion, particularly from the 20th century onwards. Consequently, it discusses the challenges that the current percussionist faces dealing with this phenomenon, from the creation and improvement of various instruments, the development of different techniques and the emergence of a vast repertoire for different instruments and musical styles, in a global context and also a Brazilian one. This means that most percussionists find themselves at some point in a paradox between the search for eclecticism when facing this huge diversity or a greater specialization in just one or a few of the instruments and/or styles addressed. It will be also discussed how percussion teaching institutions have been dealing with this specific issues.